Diagnosis and Monitoring of Hepatitis B Virus Infection Using the Cobas® HBV Test for Use on the Cobas® 4800 System - Valérie Ortonne; Mélanie Wlassow; Magali Bouvier-Alias; Giovana Melica; Jean-Dominique Poveda; Syria Laperche; Jean-Michel Pawlotsky; Stephane Chevaliez (Microorganisms, 2021)
(1) Background: Sensitive and accurate nucleic acid amplification technologies are now recommended for hepatitis B virus (HBV) DNA detection and quantification in clinical practice to diagnose and monitor hepatitis B infection. The aim of this study was to assess the analytical and clinical performance of the cobas® HBV Test on the cobas® 4800 System. (2) Methods: Standard panel and clinical specimens were tested in parallel with three different real-time commercial PCR assays including the cobas ® HBV Test, the Cobas® AmpliPrep/Cobas® TaqMan HBV Test v2.0 and Alinity™ m HBV assay. (3) Results: The specificity of the cobas® HBV Test was 97.9%. The limit of detection was estimated to be 2.1 IU/mL. Intra-assay and interassay coefficients of variation varied from 0.14% to 1.92% and 2.16% to 12.02%, respectively. HBV DNA levels in patients infected with different HBV genotypes strongly correlated with those measured by the two other commercial comparators assays. (4) Conclusions: The cobas® HBV Test can be confidently used to detect and accurately quantify HBV DNA in clinical practice as well as in clinical trials with the new anti-HBV drugs currently in development.